Efektifitas pemberian minuman jahe madu Terhadap keparahan batuk pada anak dengan ispa - Rahmadhani, Apri Nur; Novayelinda, Riri -; Woferst, Rismadefi - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
This research aims to determine the effectiveness of ginger honey ale to children with acute respiration infection (ARI) cough saverity. The method of this research is a quasi-experimental approach with non-equivalent control group. This research was conducted in the working area of Rumbai health center to 52 coughing children with ARI. There population of this study are divided into experimental group with 26 children and the control group with 26 children. The sampling method was purposive sampling using a observation shee of cough saverity. Data analized with independent t test, the result show while in the control and eksperiment group without giving ginger honey ale obtained p-value (0,001) > α (0,05) it can be concluded there is difference in the control and eksperiment group without giving ginger honey ale . The results of this study recommends to giving honey ginger ale to be one of the nursing intervention in addressing the severity of cough in children with ARI. Keywords:honey ginger ale, cough saverity